Efficacy of psychotherapy in subthreshold depression patients: A protocol for an overview of systematic reviews and meta-analyses - Han, Xu; Li, Jiaxin; Yang, Yajie; Liu, Jiaxin; Zhang, Jinzi; Han, Xiao; Reyila, Abudurousuli; Liu, Zhizhong; Ge, Pu (Frontiers in Public Health, 2022)
Background Subthreshold depression is a risk factor for major depression. Psychotherapy is a kind of intervention for subthreshold depression. There have been many systematic reviews synthesized the evidence for its effectiveness toward subthreshold depression. However, there is currently no overview of these systematic reviews. Objective To undertake an overview of meta-analyses and systematic reviews to identify the efficacy of psychotherapy in subthreshold depression patients. Methods We will search several databases such as PubMed, Embase, the Cochrane Library, Web of Science, PsycINFO, CNKI, WanFang and VIP database, for systematic reviews and meta-analyses on psychotherapy in subthreshold depression patients. The search timeline will be from inception up to August 2022. Two researchers will screen related studies back-to-back. We will include studies that evaluate the efficacy of psychotherapy in subthreshold depression patients. We will evaluate the methodological quality, the reporting quality and the quality of evidence for outcomes by AMSTAR-2, the PRISMA 2020 checklist and the GRADE grading system. We will present the results of the overview in alignment with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. The anticipated start and completion dates for this overview are 1 August 2022 and 30 December 2022, respectively. Results From this study, we will evaluate the methodological quality and the level of evidence of the included systematic reviews and meta-analyses, and evaluate the efficacy of psychotherapy in patients with subthreshold depression. Implications We will ascertain the efficacy of psychotherapy in subthreshold depression patients, to provide evidence to guide the treatment of subthreshold depression in the future. Registration number Our research protocol has been registered with PROSPERO. The registration number of the protocol is CRD42021278871.